If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3 + 6M) = 66 (3 * 3 + 6M * 3) = 66 (9 + 18M) = 66 Solving 9 + 18M = 66 Solving for variable 'M'. Move all terms containing M to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 18M = 66 + -9 Combine like terms: 9 + -9 = 0 0 + 18M = 66 + -9 18M = 66 + -9 Combine like terms: 66 + -9 = 57 18M = 57 Divide each side by '18'. M = 3.166666667 Simplifying M = 3.166666667
| 3x+76=6x-5 | | 185-5x=31x+17 | | -22-3x=13-8x | | -3-6=-5+x | | 2x+23=9x-47 | | 2(x-4)=3-5(2x+2) | | 2m+2m+2=18 | | 10-8x=130-29x | | 8+10x=71+x | | 2x+33=9x-30 | | 8x+6=4x+18 | | 81x^2-18x+2=0 | | 2[a-(2-3a)-4]=a-4 | | 3(q+2)+q=2q+5 | | 7(n+8)=8+8n | | (8m+5)(7m+8)= | | x^2-10x+50=0 | | 5d+2d=4d | | 4m+3m=53 | | 17-48=3(x-1)-4 | | 5(a+4)=28.5 | | 7y-6-8y=-12 | | 14m-3=7m+6-2m | | 9x-3x+17=35 | | 6(g+3)=(g+31) | | .9x+.05(8-x)=.10(-13) | | 2x-3-5x=8+2x-10 | | -(4x+8y+8)= | | 8-9x=35-30x | | 32=7t-15t | | 4(2s+1)-5=6s | | -8z=16 |